The Overview of Smart Contract: Legality and Enforceability - Fatihani Baso; Dzakiyah Ulya Yusuf; Andi Novita Mudriani Djaoe; Iswandi Iswandi; Anisa Ramadhany (Faculty of Law, Maranatha Christian University, 2024)
The purpose of the research is to provide an overview of the legality and enforceability of smart contracts. The research aims to examine the legal implications of the use of smart contracts in agreements. The study used qualitative research. The type of this study is normative. The second primary legal are from journals, books, and news. The recognition of the validity of smart contracts can be achieved through the setting of special clauses in contracts that recognize their validity, especially in cross-border transactions that require the addition of choice of law and choice of jurisdiction clauses. Smart contracts offer a great opportunity to revolutionize business transactions and contract law with greater efficiency and autonomy. However, for this technology to be well integrated in the legal framework, it requires the development of regulations that address the challenges of legal validity, enforceability, jurisdiction, and data security. In Indonesia, although smart contracts are permitted, legal uncertainties in various jurisdictions indicate the need for more dynamic legal adaptation to support the development of this technology.